Exploring Emerging Markets' Demographic and Macroeconomic Dynamics and the Middle Class Growth: The Case of China and India - Romana Korez Vide; Irena Zavrl; Anica Hunjet (Naše gospodarstvo/Our economy, 2021)
Emerging markets' political, economic, and social transition processes led to altered demographic trends and new macroeconomic dynamics in these economies. These changes triggered the growth of the middle class that became an essential factor of emerging markets' attractiveness for sales and production activities of foreign firms. The purpose of this article is to analyze the demographic and macroeconomic trends of China and India in the decades before the COVID-19 crisis, aimed at estimating their role in the growth of the middle class and the consequent attractiveness of these two important emerging markets for foreign firms. We formulate our research findings on the extensive theoretical foundations and empirical analysis of selected demographic and macroeconomic indicators related to the growth of the middle class. We established that India fell behind China considerably concerning demographic transition and macroeconomic dynamics in the observed periods. China enforced a radical demographic transition. The comparative analysis of macroeconomic dynamics showed a solid leadership of China in economic growth, international trade and investment openness, technological advancement, employment, the structure of the output, domestic investment, urbanization, and salaried workers. Consequently, we estimated the lower growth of the Indian middle class and its lower importance in foreign firms' decisions to enter the Indian market. The findings brought some implications for international managers at segmenting and selecting target foreign markets.